Polarization-Encoded Colocalization Microscopy at Cryogenic Temperatures - Böning, Daniel; Wieser, Franz Ferdinand; Sandoghdar, Vahid (ACS Photonics, 2021)
Super-resolution localization microscopy is based on determining the positions of individual fluorescent markers in a sample. The major challenge in reaching an ever higher localization precision lies in the limited number of collected photons from single emitters. To tackle this issue, it has been shown that one can exploit the increased photostability at low temperatures, reaching localization precisions in the subnanometer range. Another crucial ingredient of single-molecule super-resolution imaging is the ability to activate an individual emitter within a diffraction-limited spot. Here, we report on the photoblinking behavior of organic dyes at low temperature and elaborate on the limitations of this ubiquitous phenomenon for selecting single molecules. We then show that recording the emission polarization not only provides access to the molecular orientation, but it also facilitates the assignment of photons to individual blinking molecules. Furthermore, we employ periodical modulation of the excitation polarization as a robust method to effectively switch fluorophores. We benchmark each approach by resolving two emitters on different DNA origami structures.
CRIS-Team Scopus Importer:2021-02-12
Keywords: cryogenic light microscopy; DNA origami; polarization; single-molecule localization microscopy